Determination of Platelet Count Estimation Factor on Peripheral Blood Smear Confirmation Using Field Number 22 Microscope - Y. Kusumo Adi Arji Atmanto; Agus Alim Abdullah; Darwati Muhadi; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
The automatic platelet count sometimes requires confirmation on the peripheral blood smear. Platelet count estimation can also be used for reporting platelet count if an automatic cell counter is not available, with an estimation factor according to the Field Number (FN) of the microscope used. This study aimed to determine the platelet count estimation factor based on peripheral blood smear confirmation using an FN 22 microscope. An observational cross-sectional study was carried out in patients who had routine hematological and peripheral blood smear examinations during September 2021 by determination of platelet count using the automatic cell counter method and an average number of platelet counts per field of view with 100x objective magnification. The estimation factor is the total ratio divided by sample size. The total ratio of 254 samples was 4.086. The platelet count estimation factor was 16, indicating that 1 platelet per field of view was equivalent to 16x103/µL. There was a very strong significant correlation between mean platelet count per field of view and platelet count using the automatic cell counter (p<0.001, R>0.750). The field number is the image diameter of the microscope eyepiece. The latest generations of microscope use FN 20 or more, which provides a wider field of view, enabling the observation of more platelets. Factor estimation was used to determine the estimated platelet count on a peripheral blood smear. A big difference between automatic cell counter and peripheral blood smear might indicate pre-analytic, analytic, and post-analytic errors. The platelet count estimation factor based on peripheral blood smear confirmation using the FN 22 microscope was 16. Each laboratory needs to determine the estimation factor according to the FN microscope used.